Peer reactions to non-suicidal self-injury disclosures: a thematic analysis. Issue 1 (2nd January 2020) - Gayfer, Brianne L.; Mahdy, Jasmine C.; Lewis, Stephen P.
ABSTRACT: Emerging adults who engage in non-suicidal self-injury (NSSI) tend to share such experiences with peers. Thus, peers may represent a vital avenue for accessing recovery support and further help (e.g. encouraging professional help-seeking). With little known about how university students respond to NSSI disclosures from peers, the present study attempted to examine these experiences from the vantage point of disclosure recipients. Responses were gathered from a sample of undergraduate students who received an NSSI disclosure from a friend. Specifically, 104, primarily white female, emerging adults (M = 18.29 years of age, SD = .80) were recruited from a Canadian university. Demographics and open-ended questions asking about experiences receiving an NSSI disclosure from a friend were collected via online survey. Responses to the open-ended qualitative questions were examined using a thematic analysis. Responses fell broadly into four domains (intense emotional reactions, supportive responding, impact on peer relationship, and perceived insight about NSSI), which were each composed of two to four themes. Overall, findings point to several implications for researchers (e.g. developing accessible resources for peers of those who self-injure) and counselors (e.g. helping people who self-injure to understand the reactions of their peers).